1988
DOI: 10.1063/1.455587
|View full text |Cite
|
Sign up to set email alerts
|

High temperature photoelectron spectroscopy: A study of U, UO, and UO2

Abstract: The He i photoelectron spectrum of atomic uranium has been recorded in the vapor phase. Bands associated with metal (6d)−1, (7s)−1, and (5f)−1 ionizations were observed. The relative intensities of the (6d)−1 and (5f)−1 bands are consistent with computed relative cross sections at the He i energy, whereas the intensity of the (7s)−1 band is larger than expected from computed cross sections, implying enhancement of this feature by autoionization effects. HeI photoelectron spectra have also been recorded for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…[23][24][25][26][27] There have also been several theoretical studies of neutral UO 2 . 21,22,25,39,40 In contrast, theoretical studies of other actinyls are relatively scarce. 16,23,24 The partial occupancy of the 5f shell in the actinides may result in a number of low-lying states.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…[23][24][25][26][27] There have also been several theoretical studies of neutral UO 2 . 21,22,25,39,40 In contrast, theoretical studies of other actinyls are relatively scarce. 16,23,24 The partial occupancy of the 5f shell in the actinides may result in a number of low-lying states.…”
Section: Resultsmentioning
confidence: 87%
“…It was suggested that the An 6s and 6p orbitals are flexible and cannot be considered as core orbitals. 21 34 and Perdew's gradient correction for correlation (P), 35 were employed. It has been shown that the combined VWN-B-P functional can provide accurate bonding energies for both main-group 36 and transition metal 37 systems.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The photoelectron spectrum of uranium recorded with HeI radiation 21 exhibits contributions from ionization of the ground state as well as excited states populated at the high temperatures (ca. 2200 K) used for evaporation.…”
Section: Resultsmentioning
confidence: 99%
“…21 Assignments were made with the aid of Hartree-Fock-Slater (LCAO-XR) calculations. A (5f) 2 configuration was, however, assumed for the UO 2 ground state, which is different from the results obtained in later studies (including the present).…”
Section: Resultsmentioning
confidence: 99%
“…It has been an active field of research and continues to provide important experimental results concerning the electronic properties of radical species, vapor molecules and clusters in the gas phase (2,3). However, high temperature PES has been hindered by two factors, namely, the difficulty of generating high temperature species and the effect of the high temperature oven on the photoelectron measurement.…”
Section: Introductionmentioning
confidence: 99%